Women’s social networks in resettlement areas: The case of Metema resettlement site, Ethiopia - Molla, D.; Karrippai, R.S.; Puskur, Ranjitha (United Nations Economic Commission for Africa, 2010)
This study is designed to understand the existing formal and informal social networks among re-settlers in Ethiopia. Its main purpose is to explore the extent and gender implica¬tions of women’s participation in different social networks. The study aims to identify options for enhancing the role and sustainability of these social networks for promoting agricultural innovation in the Metema resettlement site in Ethiopia. Using multistage sampling procedure, the study is based on the selection of 2 out of 18 Peasant As¬sociations (PAs) in the district, and on a random sample of 160 households. The results show significant variations between previous and recent settlers, and between male and female headed households in terms of membership in different social networks. Relatives, friends and neighbors are the most important source of information and mutual support; and of influential networks in the adoption and diffusion process in the study area. The study recommends for government and NGOs to provide genuine support to social networks, to strengthen their organization, and to promote community based self help groups.